Transcriptional and translational perturbation in abiotic stress induced physiological activities and metabolic pathway networks in spongy tissue disorder of mango fruit - Oak, Pranjali; Jha, Vineet; Deshpande, Ashish; Tanpure, Rahul; Dawkar, Vishal; Mundhe, Swapnil; Ghuge, Sandeep; Prabhudesai, Shrikant; Krishanpal, Anamika; Jere, Abhay; Giri, Ashok; Gupta, Vidya (Postharvest Biology and Technology, 2022)
Spongy tissue formation is economically the most detrimental but agriculturally less focused physiological disorder in mango. `Alphonso' cultivar is highly prone to oxidative stress induced spongy tissue disorder impacting biochemical and metabolic profile, thereby affecting pulp quality and nutritional value of the fruit. In the present study, comparative analysis of spongy and healthy mesocarp tissues of `Alphonso' mango by transcriptomics using Illumina sequencing and proteomics using LC-MS approaches, respectively identified and quantified many genes and proteins in the metabolic pathways responsible for the spongy tissue development. The table green and the mid ripe stages of `Alphonso' fruit ripening were evaluated by the transcriptomic study and outcomes were validated using proteomic investigations for all the four ripening stages. Colossal amount of data including 30,582 transcripts, 10,800 gene ontologies and 387 putative proteins was generated from this analysis. Current multi-omics exploration revealed the development of abiotic stress (mainly oxidative stress) induced perturbations in various metabolic pathways and their interconnections, leading to the spongy tissue formation in mango. This further unfolded the altered cell wall degradation, ethylene and flavonoid biosynthesis, fruit ripening and flavor formation, thus hampering the fruit specific characteristics in mango with spongy tissue disorder.
Keywords: Oxidative stress; Proteome; spongy tissue disorder; Transcriptome; ` Alphonso ` mango